Profitability Performance of BUMN Banks and Bank Health Level - Pujiati, Desi; Chaerunnisa, Chaerunnisa (P3KM Politeknik Pertanian Negeri Samarinda, 2023)
Bank health is one measure of financial performance achievement. Success in managing assets in banking companies is measured by the level of profitability in the Return On Assets ratio. Profitability can be achieved with healthy financial conditions. Good bank health with good management, bad credit ratio which is below the provisions of the OJK, sufficient capital ratio. The aim of this research is to examine in more depth how much profitability achieved is influenced by the level of bank health on profitability at BUMN commercial banks. BUMN banks are the main supporter of government banking services with private management. The choice of secondary data in financial reports is needed to obtain bank health and profitability ratios. An analytical tool that can measure whether there is an influence between the level of bank health and profitability using multiple linear analysis. The research findings confirm that GCG at BUMN banks in Indonesia has an influence on achieving profitability. The GCG Value Assessment produces the highest average GCG rating of 1. This high assessment is because BUMN banks are able to implement GCG principles to achieve accountable profitability. NIM influences the Profitability (ROA) management ability of BUMN banks in Indonesia in terms of revenue performance in a healthy condition with an average of above five percent. The healthy level of NPLs in BUMN banks with an average yield of three percent has no effect on profitability performance. Profitability (ROA) at BUMN banks is not influenced by capital management from achieving the CAR ratio.